2017
DOI: 10.1007/s12011-017-1140-x
|View full text |Cite
|
Sign up to set email alerts
|

Copper, Manganese, Zinc, and Cadmium in Tea Leaves of Different Types and Origin

Abstract: Concentrations of selected metals (Cu, Mn, Zn, Cd) in tea leaves were investigated. Samples included black, green, and other (red, white, yellow, and oolong) teas. They were purchased on a local market but they covered different countries of origin. Beverages like yerba mate, rooibos, and fruit teas were also included in the discussion. Metal determinations were performed using atomic absorption spectrometry. In black teas, Mn/Cd ratio was found to be significantly higher (48,091 ± 35,436) vs. green (21,319 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 9 publications
7
12
1
Order By: Relevance
“…Some studies have reported lower levels of PTEs in green tea than black tea; our findings were in line with these studies (Barone et al, 2016;Podwika et al, 2018). The level of Pb in green tea samples (0.47 ± 0.07 mg kg −1 ) analyzed by Barone et al (2016) was lower than that of black tea (0.55 ± 0.35 mg kg −1 ), although de Oliveira et al (2018) reported higher Pb level in green tea (0.76 ± 0.12 mg kg −1 ) while compared with black tea (0.64 ± 0.11 mg kg −1 ) (Barone et al, 2016;de Oliveira et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Some studies have reported lower levels of PTEs in green tea than black tea; our findings were in line with these studies (Barone et al, 2016;Podwika et al, 2018). The level of Pb in green tea samples (0.47 ± 0.07 mg kg −1 ) analyzed by Barone et al (2016) was lower than that of black tea (0.55 ± 0.35 mg kg −1 ), although de Oliveira et al (2018) reported higher Pb level in green tea (0.76 ± 0.12 mg kg −1 ) while compared with black tea (0.64 ± 0.11 mg kg −1 ) (Barone et al, 2016;de Oliveira et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Many authors confirm the significant role of tea infusions, demonstrated in this study, in providing the amount of manganese recommended for daily intake [ 25 , 30 ], while Brzezicha-Cirocka et al [ 31 ] also indicate that they may provide the body with a noticeable level of copper, magnesium, and zinc, and only a very small amount of calcium and sodium.…”
Section: Resultssupporting
confidence: 74%
“…The variation in the level of minerals in various tea infusions has been indicated by numerous authors [ 7 , 10 , 25 , 26 , 28 , 29 , 30 , 31 ] who, besides the tea production method, also noted other factors impacting this variation such as the variety, location and method of leaf cultivation and the duration and technique of harvesting, storage and transport. The differences in the content of minerals shown by the authors depend to a large extent on the type of tea leaves available in the country, and the differences between them may be several- [ 10 , 29 ], several dozen- [ 31 ] or even several hundred-fold [ 30 ].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The other sources of this mineral are vegetables, potatoes, fruit and tea [64,96]. Especially very common in Poland habitual drinking of tea infusions may significantly contribute to the meeting of the reference value for manganese [97,98,99]. However, manganese is an essential nutrient due to its role [10,12,13,14,15] in terms of the metabolism of carbohydrates, amino acids, and cholesterol [10,16,17] as well as many functions of different systems [14,15,16].…”
Section: Discussionmentioning
confidence: 99%